Human Calmodulin Mutations - Jensen, Helene H.; Brohus, Malene; Nyegaard, Mette; Overgaard, Michael T. (Frontiers in Molecular Neuroscience, 2018)
Fluxes of Ca2+ across cell membranes enable fast cellular responses. Calmodulin (CaM) senses local changes in Ca2+ concentration and relays the information to numerous interaction partners. The critical role of accurate Ca2+ signaling on cellular function is underscored by the fact that there are three independent CaM genes (CALM1-3) in the human genome. All three genes are functional and encode the exact same CaM protein. Moreover, CaM has a completely conserved amino acid sequence across all vertebrates. Given this degree of conservation, it was long thought that mutations in CaM were incompatible with life. It was therefore a big surprise when the first CaM mutations in humans were identified six years ago. Today, more than a dozen human CaM missense mutations have been described, all found in patients with severe cardiac arrhythmias. Biochemical studies have demonstrated differential effects on Ca2+ binding affinities for these CaM variants. Moreover, CaM regulation of central cardiac ion channels is impaired, including the voltage-gated calcium channel, CaV1.2, and the sarcoplasmic reticulum Ca2+ release channel, RyR2. Currently, no non-cardiac phenotypes have been described for CaM variant carriers. How-ever, sequencing of large human cohorts reveals a cumulative frequency of additional rare CaM mutations that raise the possibility of CaM variants not exclusively causing severe cardiac ar-rhythmias. Here, we provide an overview of the identified CaM variants and their known conse-quences for target regulation and cardiac disease phenotype. We discuss experimental data, patient genotypes and phenotypes as well as which questions remain open to understand this complexity.